2020
DOI: 10.1177/1740774520902741
|View full text |Cite
|
Sign up to set email alerts
|

Broadening community engagement in clinical research: Designing and assessing a pilot crowdsourcing project to obtain community feedback on an HIV clinical trial

Abstract: Background/Aims Community engagement is widely acknowledged as an important step in clinical trials. One underexplored method for engagement in clinical trials is crowdsourcing. Crowdsourcing involves having community members attempt to solve a problem and then publicly sharing innovative solutions. We designed and conducted a pilot using a crowdsourcing approach to obtain community feedback on an HIV clinical trial, called the Acceptability of Combined Community Engagement Strategies Study. In this work, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Other studies have explored the adoption of participatory methods for developing informed consent. Recently, a crowdsourcing approach was used to highlight the limits of the informed consent used for HIV clinical trials and propose alternative formats, through workshops that, however, were not based on design thinking ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have explored the adoption of participatory methods for developing informed consent. Recently, a crowdsourcing approach was used to highlight the limits of the informed consent used for HIV clinical trials and propose alternative formats, through workshops that, however, were not based on design thinking ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two excellent tools for public engagement are infographics and videos [ 6 , 24 ]. These complementary tools are commonly accepted at major medical journals and may be useful for engaging public audiences.…”
Section: Co-creating Infographics and Videosmentioning
confidence: 99%
“…Videos have the advantage of reaching some audiences who may not read medical research journals, including individuals for whom English is a second language and those who face socioeconomic barriers [ 6 , 31 , 32 ]. Short videos co-created with the public suggest new ways to empower groups that are underrepresented in research [ 24 , 31 , 33 ].…”
Section: Co-creating Infographics and Videosmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Randomized clinical trials have demonstrated the effectiveness of crowdsourcing across an array of health topics, 9 and social science research has shown that open calls can enhance community engagement through the meaningful participation of a broad range of local stakeholders. 10 , 11 For example, a crowdsourcing open call on the topic of HIV cure research resulted in creative contributions from local stakeholders and the development of messaging around HIV cure research that was both culturally appropriate and resonated with communities that are disproportionately impacted by HIV. 12 In addition, compared with other community engagement mechanisms (eg, community advisory boards), crowdsourcing open calls have been found to engage a broader range of stakeholders whose perspectives are often underrepresented in health and medical research, including individuals with lower levels of education and lower incomes.…”
Section: Introductionmentioning
confidence: 99%